Shelf-life of Dahi (Yogurt) with or without potato mash (Bangladesh Veterinarian, 2012)
Four different types of Dahi (Yogurt) were prepared and kept at room and   refrigeration temperatures with different concentrations of potato mash (0, 5, 10 and 15%). These Dahi samples were analyzed for smell and taste, body and consistency, colour, texture and acidity and pH at pre and post storage period. The quality of Dahi deteriorated quickly at room temperature than at refrigeration temperature. With (5%) or without potato mash keeping quality was preserved for up to three days but at refrigeration temperature they were suitable up to 12 days. Addition of 10% and 15% potato mashes were suitable for keeping Dahi up to two days at room temperature while in refrigeration temperature it was acceptable up to ten and eight days, respectively. Preparation of Dahi in incorporating potato mash may be economically feasible without compromising it qualities. DOI: http://dx.doi.org/10.3329/bvet.v29i1.11886 Bangl. vet. 2012. Vol. 29, No. 1, 22-30